A Unique Case of Relapsed B-Acute Lymphoblastic Leukemia/Lymphoma as an Isolated Omental Mass - Kanchan Kantekure; Furha Cossor; Kenneth B. Miller; Monika E. Pilichowska (Case Reports in Hematology)
B-acute lymphoblastic leukemia/lymphoma (B-ALL) is a neoplasm of precursor cells committed to the B-cell lineage. Extramedullary involvement is frequent, with particular predilection for the central nervous system, lymph nodes, spleen, liver, and testis. We report an unusual case of B-ALL relapsing as an isolated omental mass along with bone marrow involvement.